2021
DOI: 10.3390/nu13113698
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Probiotic PS128 in Children with Tourette Syndrome

Abstract: Tourette syndrome results from a complex interaction between social–environmental factors, multiple genetic abnormalities, and neurotransmitter disturbances. This study is a double-blinded, randomized controlled trial using probiotics Lactobacillus plantarum PS128 as an intervention to examine if probiotics improve symptoms of children with Tourette syndrome. This study enrolled children aged 5 to 18 years old who fulfilled DSM-V diagnostic criteria for Tourette syndrome. Patients were assessed before initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…TS is a neurological disorder that generally develops at the age of 6–18 years. In this syndrome, patients show repetitive behavior like unwanted sounds (tics), repetitive blinking of eyes, abnormal muscle activity, anxiety, and random mood swings [1, 2]. TS has a significant impact on a patient’s mental health and social behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TS is a neurological disorder that generally develops at the age of 6–18 years. In this syndrome, patients show repetitive behavior like unwanted sounds (tics), repetitive blinking of eyes, abnormal muscle activity, anxiety, and random mood swings [1, 2]. TS has a significant impact on a patient’s mental health and social behavior.…”
Section: Discussionmentioning
confidence: 99%
“…for the treatment of TICS. Various reviews and meta-analyses [1][2][3][4][5] reported the safe and efficient use of these TCMs to treat TICS associated with Tourette Syndrome (TS) with minimal side effects. However, the evidence regarding the TCMs' effectiveness and safety in the treatment of TS is still conflicting due to the limited number of results reported, use of unblinded assessments, lack of sophisticated analysis, and evidencelevel GRADE assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that this study was based on participant self-reports, more study on this topic is necessary. The treatment of tics with the addition of certain foods or supplements has also been attempted, such as probiotics, N-acetyl cysteine, and omega-3 fatty acids, but results have generally not shown significant improvements [ 73 , 74 , 75 ]. One open-label study did show improvement in tics in patients given L-Theanine and Vitamin B6 as compared with a control condition of psychoeducation [ 76 ].…”
Section: “Just the Facts Ma’am” What’s The Evidence About What Situat...mentioning
confidence: 99%
“…Probiotic drugs, in the form of feed additives, are increasingly used in the fattening of animals and poultry for therapeutic and prophylactic purposes (Martyshuk et al, yeast, etc. (Ashayerizadeh et al, 2009;Molnar et al, 2011;Wieërs et al, 2020;Wu et al, 2021;Wan et al, 2021). Their action is based on the high activity of these strains of microorganisms to pathogenic and opportunistic microflora (even insensitive to many antibiotics), the ability to activate macrophages, and the induction of interferons (Griggs & Jacob, 2005;Ushakova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%